2018
DOI: 10.1159/000493412
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Exerts a Protective Effect on Gut-Vascular Barrier via the Modulation of the Wnt/Beta-Catenin Signaling Pathway During Sepsis

Abstract: Background/Aims: The gut-vascular barrier (GVB) has recently been depicted to dampen the bacterial invasion of the bloodstream. The intestinal mucosa is a tissue rich in small vessels including capillaries. In this study, the protective effect of berberine on GVB in small bowel mucosa was investigated. Methods: The rat cecal ligation and puncture (CLP) sepsis model was employed to evaluate the effect of berberine on serum endotoxin level and intestinal vascular permeability to Evans blue in vivo. The rat intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Finally, our results showing no extravasation in BRB-treated animals indicate that this natural compound may affect the angiogenic process without affecting vascular permeability during embryonic development, in line with results previously reported in VEGF-treated quail embryos 56 . In addition, results in vivo in rodents and in vitro in rat microvascular endothelial cells indicated that BRB may counteract vascular permeability 33,57,58 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our results showing no extravasation in BRB-treated animals indicate that this natural compound may affect the angiogenic process without affecting vascular permeability during embryonic development, in line with results previously reported in VEGF-treated quail embryos 56 . In addition, results in vivo in rodents and in vitro in rat microvascular endothelial cells indicated that BRB may counteract vascular permeability 33,57,58 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, data on BBR effects on Cdh5 are very limited at present. BRB treatment has been reported to counteract the reduction of Cdh5 protein levels induced in vitro by lipopolysaccharide in rat intestinal microvascular endothelial cells 33 . In addition, the BRB-type natural alkaloid Coptisine inhibited the expression of Cdh5 in vitro in a human osteosarcoma cell line, at both mRNA and protein level 34 .…”
mentioning
confidence: 99%
“…Intestinal vascular endothelial cells are important part of the intestinal mucosa. Different connexins are the key factors to maintain the stability of endothelial cells and maintain the permeability of the intestine [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Berberine is an alkaloid extracted from the root and bark of Rhizoma coptidis and Cortex phellodendri and is known for its remedial properties in bacterial infections and gastrointestinal disorders 17,18 . Berberine has been shown to have anti‐inflammatory properties and has drawn attention as an agent for the treatment of sepsis.…”
Section: Treatment Of Sepsis With Polyphenolic Compoundsmentioning
confidence: 99%